2020
DOI: 10.1002/ange.201916321
|View full text |Cite
|
Sign up to set email alerts
|

Landornamides: Antiviral Ornithine‐Containing Ribosomal Peptides Discovered through Genome Mining

Abstract: Proteusins are a family of bacterial ribosomal peptides that largely remain hypothetical genome‐predicted metabolites. The only known members are the polytheonamide‐type cytotoxins, which have complex structures due to numerous unusual posttranslational modifications (PTMs). Cyanobacteria contain large numbers of putative proteusin loci. To investigate their chemical and pharmacological potential beyond polytheonamide‐type compounds, we characterized landornamide A, the product of the silent osp gene cluster f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In addition, with the knowledge of the NRPS and RiPP machineries combined, we envision the merging of these two natural peptide product worlds, either by creating non-ribosomal antimicrobial peptide structures with a RiPP machinery, or combining RiPP tailoring enzymes with NRPS megasynthetases [90,116]. The potential of the former approach has recently been explored by the functional mimicking of the NRP brevicidine with a RiPP machinery [117,118].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, with the knowledge of the NRPS and RiPP machineries combined, we envision the merging of these two natural peptide product worlds, either by creating non-ribosomal antimicrobial peptide structures with a RiPP machinery, or combining RiPP tailoring enzymes with NRPS megasynthetases [90,116]. The potential of the former approach has recently been explored by the functional mimicking of the NRP brevicidine with a RiPP machinery [117,118].…”
Section: Discussionmentioning
confidence: 99%
“…The potential of the former approach has recently been explored by the functional mimicking of the NRP brevicidine with a RiPP machinery [117,118]. Moreover, the possibility of introducing D-amino acids, methylation, glycosylation, several side chain cross-links, non-canonical amino acids as well as fatty acids on antimicrobial peptide scaffolds will further expand this approach, given SAR studies of a carefully chosen antimicrobial NRP scaffold as well as detailed knowledge on leader requirements and promiscuity of the RiPP machinery are known [90,113,[118][119][120][121][122]. Interestingly, also the first examples of natural hybrid biosynthetic clusters involving both NRPS and RiPPs elements have been described [119,123,124].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first representative of this family was polytheonamide, from an uncultivated sponge symbiont (see above), but a genomic survey of cyanobacterial genomes revealed the presence of over 50 proteusin-like BGCs in cyanobacteria, many of them with multiple precursor peptides. Expression of one of these clusters in E. coli resulted into the production of landornamides ( Figure 12 ), the first characterized cyanobaterial proteusin [ 293 ]. Similarly, the spliceotide family was identified in cyanobacteria after genomic studies revealed the presence of clusters containing nif11 domain-containing precursor peptides, associated with orphan radical SAM enzymes.…”
Section: Cyanobacteriamentioning
confidence: 99%